Pemanfaatan MIDI dalam Rekaman dan Pertunjukan Musik - I Pt. Lukita Wiweka Nugraha Putra; Komang Wahyu Dinata (Journal of Music Science, Technology, and Industry, 2025)
Purpose: The topic of this research is the use of MIDI in recording and musical performances in general, and in Bali in particular. This research focuses on how MIDI technology makes the process of recording and musical performances run effectively and efficiently. Method: The approach used in this research is a qualitative approach. The phenomenon of the use of MIDI in recording and musical performances is the subject of study in this research. Documentation studies were conducted by researching musical recordings and performances in Bali. The data analysis technique used is qualitative descriptive analysis, namely analyzing data that has been obtained through qualitative descriptive analysis. Result and Discussion: The recording process using MIDI will be more effective and efficient, because it allows for maximum results without requiring a lot of costs to present musical instruments such as bass, orchestra, drums, and others. Likewise, in musical performances, composers can use MIDI as an alternative to real instruments with various media such as keyboards, pads, MIDI guitars, and others. Implication: In the era of globalization, technology is a necessity, including the need for musical artists or musicians to realize their works. The realization of musical works can be done through recording and performance activities. MIDI, as a technological product, can be a solution for composers and musicians in creating musical works. MIDI can make the process of recording and performing musical works effective and efficient.